A Comparative Analysis of Relationship Between Hypothyroidism and Platelet Parameters Including Platelet Indices, Platelet Distribution Width, Plateletcrit and P-LCR - Amitkumar, P Kalaivani; Swaminathan, Anandhalakshmi; Priya, G Geetha; Ganapathy, Shivashekar (Annals of Pathology and Laboratory Medicine, 2018)
Background: Patients with hypothyroidism are at increased risk of haemorrhage and there is a tendency to develop thromboembolic complications. MPV which is an indicator of platelet activity can act as an individual independent risk factor for cardiovascular complications. Identification of changes in these parameters using automated cell counters are proved to be cost effective and routinely done during clinical practice. This study is aimed to evaluate the influence of hypothyroidism on platelet indices including platelet count, MPV, PDW, plateletcrit and P-LCR and to compare the results with age matched normal euthyroid subjects. Methods: Prospective cross-sectional study was conducted for a period of 8 months between 60 hypothyroid subjects and 60 normal adults as a control group. Demographic details were compared between the groups. Fasting blood sample was collected to determine thyroid profile. Complete blood count (CBC) including platelet indices and peripheral smear examination were done. Results: Male: female ratio was 1:8.6 %, The median age was 43 with a range of 34–52 years. Among the baseline data actual difference was not statistically significant. On comparing with control group T3 and T4 values showed statistically significant decrease (p<0.00 and 0.006), and TSH value shows statistically significant increase in (p<0.00) values. Statistically significant increase was noted in MPV (p<0.03, t value 2.165) and platelet distribution width (p<0.02, t value 2.334). Significant p values were not found in platelet count (p<0.22, t value 1.238) P-LCR (p<0.48, t value 0.697) and PCT p <0.24, t value 1.188) among the groups. Conclusion: Our results suggest that MPV and PDW are the reliable markers among the platelet parameters, can be used as a CVD risk evaluation parameters in hypothyroid patients.